2011
DOI: 10.1002/ange.201103224
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Borylation of Sterically Demanding Aryl Halides with a Silica‐Supported Compact Phosphane Ligand

Abstract: Unbeweglich, aber aktiv: Ein Siliciumoxid‐gebundenes „kompaktes“ Phosphan, Silica‐SMAP, wurde für die Pd‐katalysierte Borylierung von Arylchloriden und ‐bromiden mit Bis(pinakolato)dibor genutzt (siehe Schema). Das Silica‐SMAP/Pd‐System erweitert das Substratspektrum der Borylierung auf sterisch und elektronisch anspruchsvolle Arylhalogenide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…26 Initial investigation for the coupling of bis(pinacolato)diboron conducted with 10 found that the aryl chlorides underwent oxidative addition as evidenced by the generation of reduction products, but only trace amounts of a mono-borylated product could be detected. Attempts to increase the reaction temperature and times only led to over reduction of both the C- and E-ring aryl chlorides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Initial investigation for the coupling of bis(pinacolato)diboron conducted with 10 found that the aryl chlorides underwent oxidative addition as evidenced by the generation of reduction products, but only trace amounts of a mono-borylated product could be detected. Attempts to increase the reaction temperature and times only led to over reduction of both the C- and E-ring aryl chlorides.…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to increase the reaction temperature and times only led to over reduction of both the C- and E-ring aryl chlorides. Adoption of borylation conditions 26e using tetrahyroxydiboron (X-Phos, B 2 (OH) 4 , EtOH, 80 °C, 3 h)with 6 provided a 1:1 ratio of a single mono-borylated product 12 with reduction of the second aryl chloride, and the bis-borylated product 13 (Figure 4). By decreasing the reaction time, the reduction of the second chloride was diminished leading to the observance of a single mono-borylated product with the second aryl chloride intact.…”
Section: Resultsmentioning
confidence: 99%
“…[16] The formation of organic-inorganic hybrid nanocrystals was first evidenced by high-resolution transmission electron microscopy (HRTEM; Figure 1 B), thus revealing the presence of small spherical palladium NCs with a narrow size distribution (3.6 AE 0.6) nm (Figures 1 B and C). Complexation of the ligand to the palladium surface was proven by conducting 1 H, 13 C, 19 F, and 31 P NMR experiments (Figure 1 D and see the Supporting Information). 1 H NMR spectra of dppf-complexed NPs show signals for the cyclopentadienyl moiety at d = 4.76 and 4.30 ppm.…”
mentioning
confidence: 99%
“…Complexation of the ligand to the palladium surface was proven by conducting 1 H, 13 C, 19 F, and 31 P NMR experiments ( Figure 1 D and see the Supporting Information). Moreover, the 13 C NMR spectra and complementary 19 F NMR spectra show the absence of residual hfa ligands or related degradation products. Compared to the signals in the 1 H NMR spectra of free dppf at d = 4.27 and 4.01 ppm, a clear upfield shift is observed, and is caused by a downfield shielding effect resulting from the complexation of the organic molecule to the metallic core.…”
mentioning
confidence: 99%
“…[17] A similar shielding effect is also detected in the 31 P NMR spectra of the free dppf (d = À16.8 ppm) compared to the NCs-ligated dppf (d = 28.1 ppm; Figure 1 D). [19] This work would offer a new synthetic route to afford highly reactive borylated species. HRTEM and NMR studies evidence the composition and morphology of the palladium NCs complexed with dppf.…”
mentioning
confidence: 99%